The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acsami.2c06653
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Growth of High-Quality CsPbBr3 Quantum Dots with Unusual Morphology inside a Transparent Glass with a Heterogeneous Crystallization Environment for Wide Gamut Displays

Abstract: All-inorganic CsPbBr3 perovskite quantum dots (QDs) are considered to be one of the most promising green candidates for the new-generation backlight displays. The pending barriers to their applications, however, lie in their mismatching of the target window of green light, scalable production, susceptibility to the leaching of lead ions, and instability in harsh environments (such as moisture, light, and heat). Herein, high-quality CsPbBr3 QDs with globoid shapes and cuboid shapes were in situ crystallized/gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…To date, all-inorganic CsPbX 3 (X = Cl, Br, and I) perovskite QDs (PeQDs) have been successfully precipitated in a variety of glasses via in situ nucleation/growth. [32][33][34][35][36][37][38][39] However, unlike wet-chemical synthesis, the dense glass network structure will hinder the diffusion of Cs + , Pb 2+ , and X − ions, and impede CsPbX 3 nanocrystallization inside glass, which makes PLQYs of CsPbX 3 @glass lower than those of colloidal counterparts. Herein, we have successfully optimized SiO 2 -B 2 O 3 -ZnO-CaF 2 glass network, perovskite component concentrations, and glass crystallization conditions to fabricate high-quality CsPbX 3 @glass.…”
Section: Introductionmentioning
confidence: 99%
“…To date, all-inorganic CsPbX 3 (X = Cl, Br, and I) perovskite QDs (PeQDs) have been successfully precipitated in a variety of glasses via in situ nucleation/growth. [32][33][34][35][36][37][38][39] However, unlike wet-chemical synthesis, the dense glass network structure will hinder the diffusion of Cs + , Pb 2+ , and X − ions, and impede CsPbX 3 nanocrystallization inside glass, which makes PLQYs of CsPbX 3 @glass lower than those of colloidal counterparts. Herein, we have successfully optimized SiO 2 -B 2 O 3 -ZnO-CaF 2 glass network, perovskite component concentrations, and glass crystallization conditions to fabricate high-quality CsPbX 3 @glass.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the data provided by Li et al as shown in Figure , a gradual drop in PL intensity and slightly blue-shifted PL peak were observed as the temperature increased (Figure a and b), which is due to the thermal expansion of the perovskite nanocrystals and the electron–phonon interactions that lead to an increase in the band gap. , Further examinations of the photostability of the composites under continuous irradiation and ambient conditions were also carried out by Li and co-workers. And it was demonstrated that these CsPbBr 3 NCs@glass composites showed quite high stability for a 365-day test under ambient conditions (Figure f) and maintained 71.42 and 68.29% of the initial PL intensity in the case of 186 h of continuous irradiation under UV or blue lamp irradiation (Figure d and e) . Li et al also tested their CsPbBr 3 NCs@glass composites on backlight display applications.…”
Section: In Situ Growth Of Cspbbr3 Ncs Inside Glassmentioning
confidence: 97%
“…(g, h) Application of white LED strips constructed utilizing the YAG:Ce 3+ (YAG) (commercial) and CsPbBr 3 NCs@glass backlight units in an LCD screen. All panels are reproduced from ref . Copyright 2022 American Chemical Society.…”
Section: In Situ Growth Of Cspbbr3 Ncs Inside Glassmentioning
confidence: 99%
“…As the display industry continues to evolve, the market puts forward higher requirements on the performance of display devices. All inorganic perovskite CsPbX 3 (X = Cl, Br, I) nanocrystal (NC) materials exhibit distinguished optical properties, including high carrier mobility, size-tunable emission, narrow full width at half-maximum (fwhm), and high photoluminescence quantum yield (PLQY). , Over the past few years, they have been consistently identified as emerging frontiers, particularly in the area of backlight display applications, generating significant interest among researchers. However, the instability of perovskite quantum dots (QDs), particularly their sensitivity to environmental conditions such as water, heat, light, and oxygen, significantly hinders their potential applications. To keep pace with industrial development, it is imperative to optimize the performance and stability of perovskite QDs.…”
Section: Introductionmentioning
confidence: 99%